Use of social media by healthcare professionals in Greece: an exploratory study. (18th October 2012) - Apostolakis, Ioannis; Koulierakis, George; Berler, Alexander; Chryssanthou, Anargyros; Varlamis, Iraklis
The continuously and rapidly changing landscape in the fields of communications, Internet and social media make it imperative for professionals to better understand the role of Information and Communication Technologies and their impact on everyday activities. Several frameworks have been proposed in order to capture various dimensions of social media and measure their impact on people's social, professional and other activities. The effect of social media and Web 2.0 applications on the healthcare sector is also significant. This paper examines Greek healthcare professionals' attitudes towards internet, social media and mobile technologies, explores their familiarity with social networks and associates their answers with their professional profile. The results of this exploratory study are discussed within the context of the growing international relevant literature.